2016
DOI: 10.1038/srep39393
|View full text |Cite
|
Sign up to set email alerts
|

HtrA2 suppresses autoimmune arthritis and regulates activation of STAT3

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease that is related to the induction of T helper (Th)17 cells, which secrete interleukin-17, and activation of the signal transducer and activator of transcription (STAT) 3. The expression of high-temperature requirement protein A (HtrA) 2, a serine protease involved in apoptosis, was decreased in RA patients nonresponsive to drug treatment of RA. The aim of this study was to determine whether overexpression of HtrA2 has a therapeutic effect on RA. Th17 differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Th17 cells are pathogenic factors in several autoimmune diseases, and inhibition of Th17 cell differentiation diminishes inflammatory disorders [ 29 31 ]. Downregulation of Th17 cell populations leads to attenuation of CIA [ 32 ]. On the other hand, Treg cells show an immunosuppressive function; thus, a reciprocal balance between Th17 and Treg cells is important to diminishing CIA [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells are pathogenic factors in several autoimmune diseases, and inhibition of Th17 cell differentiation diminishes inflammatory disorders [ 29 31 ]. Downregulation of Th17 cell populations leads to attenuation of CIA [ 32 ]. On the other hand, Treg cells show an immunosuppressive function; thus, a reciprocal balance between Th17 and Treg cells is important to diminishing CIA [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that HTRA2 suppresses cell proliferation through binding to WARTS (WTS)/large tumor-suppressor 1 mitotic kinase (Kuninaka et al, 2007). HTRA2 cleaves STAT3 protein to modulate expression of cytokines that regulate T cell proliferation (Lee et al, 2016). These studies indicate that HTRA2 cleaves multiple substrates, including proteins that directly regulate the cell cycle, or indirectly, through modulating activity of transcription factors involved in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of STAT3 leads to increased proinflammatory cytokine production and immune responses (11, 12). Recent reports have shown that inhibition of STAT3 improves experimental autoimmune arthritis by limiting the immune–inflammatory response (1315). STAT3 activation has also been shown to be significantly higher in chondrocytes from OA patients than in those from normal controls (16).…”
Section: Introductionmentioning
confidence: 99%